Retroperitoneal Ganglioneuroma with Multifocal Bone Involvement in a Middle-Aged Woman - Watanabe, Hiroki (Hinyokika kiyo. Acta urologica Japonica, 2025)
Ganglioneuroma, an infrequent benign tumor that originates from the sympathetic nervous system, is usually a solitary occurrence and rarely occurs at multiple sites. Here, we report a case of retroperitoneal ganglioneuroma with multifocal bone involvement in a middle-aged woman. A 43-year-old female was incidentally diagnosed with a retroperitoneal tumor on abdominal ultrasonography. Contrast-enhanced computed tomography revealed a retroperitoneal tumor that was 11 cm in diameter above her left kidney and multiple bone lesions. Fluorodeoxyglucose positron emission tomography (FDG-PET) showed a slightly high FDG uptake (standardized uptake value (SUV) max, 3.7) in the retroperitoneal mass and mild accumulation in the L1 vertebral body, zygoma, acetabulum, and calcaneus. Biopsies were performed for the retroperitoneal and lumbar spine tumors, both of which were diagnosed as ganglioneuromas. Total surgical resection is the standard treatment of this condition ; however, for this patient, it was difficult to remove all the tumors, and the ganglioneuromas generally followed a benign course. Therefore, a watchful waiting approach was chosen and no tumor growth was observed three years after her first visit to our hospital